Amperometric determination of myo-inositol by using a glassy carbon electrode modified with molecularly imprinted polypyrrole, reduced graphene oxide and nickel nanoparticles - Beluomini, Maísa Azevedo [UNESP] (2018)
This paper reports on the development of an amperometric method for the determination of myo-inositol. The method involves coating of a glassy carbon electrode (GCE) with a molecularly imprinted polymer (MIP) and reduced graphene oxide (RGO) that was modified with nickel nanoparticles (NiNPs). The MIP was prepared by electropolymerization of pyrrole on the surface of the GCE in the presence of myo-inositol molecules. The construction steps of the modified electrode were monitored via cyclic voltammetry, atomic force microscopy, scanning electron microscopy and X-ray Photoelectron Spectroscopy. The results were evaluated using differential pulse voltammetry, in which hexacyanoferrate was used as an electrochemically active probe. Under optimized experimental conditions, the imprint-modified GCE has a linear response in the 1.0 × 10−10 mol L−1 to 1.0 × 10−8 mol L−1 concentration range, with a 7.6 × 10−11 mol L−1 detection limit and an electrochemical sensitivity of 4.5 μA·cm-2 μmol−1. The method showed improved selectivity even in the presence of molecules with similar chemical structure. The GCE modified was successfully applied to the determination of myo-inositol in sugarcane vinasse where it yielded recoveries that ranged from 95 to 102%. [Figure not available: see fulltext.].